Exploration of Using Antisense Peptide Nucleic Acid (PNA)-cell Penetrating Peptide (CPP) as a Novel Bactericide against Fire Blight Pathogen Erwinia amylovora - Patel, Ravi R.; Sundin, George W.; Yang, Ching-Hong; Wang, Jie; Huntley, Regan B.; Yuan, Xiaochen; Zeng, Quan (Frontiers in Microbiology, 2017)
Erwinia amylovora is a Gram-negative bacterial plant pathogen in the family Enterobacteriaceae and is the causal agent of fire blight, a devastating disease of apple and pear. Fire blight is traditionally managed by the application of the antibiotic streptomycin during bloom, but this strategy has been challenged by the development and spread of streptomycin resistance. Thus, there is an urgent need for effective, specific, and sustainable control alternatives for fire blight. Antisense antimicrobials are oligomers of nucleic acid homologs with antisense sequence of essential genes in bacteria. The binding of these molecules to the mRNA of essential genes can result in translational repression and antimicrobial effect. Here, we explored the possibility of developing antisense antimicrobials against E. amylovora and using these compounds in fire blight control. We determined that a 10-nucleotide oligomer of peptide nucleic acid (PNA) targeting the start codon region of an essential gene acpP is able to cause complete growth inhibition of E. amylovora. We found that conjugation of cell penetrating peptide (CPP) to PNA is essential for the antimicrobial effect, with CPP1 [(KFF)3K] being the most effective against E. amylovora. The minimal inhibitory concentration (MIC) of anti-acpP-CPP1 (2.5 µM) is comparable to the MIC of streptomycin (2 µM). Examination of the antimicrobial mechanisms demonstrated that anti-acpP-CPP1 caused dose-dependent reduction of acpP mRNA in E. amylovora upon treatment and resulted in cell death (bactericidal effect). Anti-acpP-CPP1 (100 µM) is able to effectively limit the pathogen growth on stigmas of apple flowers, although less effective than streptomycin. Finally, unlike streptomycin that does not display any specificity in inhibiting pathogen growth, anti-acpP-CPP1 has more specific antimicrobial effect against E. amylovora. In summary, we demonstrated that PNA-CPP can cause an effective, specific antimicrobial effect against E. amylovora and may provide the basis for a novel approach for fire blight control.